Investigation of Physical, Mechanical Properties of Treated Date Palm Fibre and Kenaf Fibre Reinforced Epoxy Hybrid Composites - Syed Waheedullah Ghori; Gunji Srinivasa Rao; Ali A Rajhi (Journal of Natural Fibers, 2023)
This research is a comparative study of untreated and treated date palm fiber (DPF) and kenaf (KF)-reinforced epoxy hybrid composite and explores the properties of DPF. The prepared hybrid composites were characterized in terms of tensile properties, impact properties, physical behavior, water absorption, and thickness swelling. The composites were prepared by hand layup technique. Treated 30% date palm and 70% kenaf (T-3DP7K) showed the highest tensile strength (26.45 MPa) and modulus (4.54 GPa) among untreated and treated hybrid composites. The scanning electron microscope revealed the behavior of fiber and polymers and also the cause of tensile test failure. The impact strength of T-1DP1K revealed highest impact resistant (5493 J/m) among untreated and treated hybrid composites. Remarkably, alkali-treated hybrid composites reduced the water absorption and thickness swelling compared to the untreated composites. In untreated composites, higher DPF content composites showed higher moisture content and dimensional instability. Overall, we concluded that among all hybrid composites, T-3DP7K showed better tensile properties, lowest water absorption, and lowest thickness swelling, and T-7DP3K showed better impact properties.